Pontoniine Shrimps (Crustacea: Decapoda: Palaemonidae) from the CReefs 2009 Heron Island Expedition, with a review of the Heron Island pontoniine fauna - Bruce, A. J. (Zootaxa, 2010)
Recent collections of pontoniine shrimps from Heron Island, southern Great Barrier Reef, have provided further additions to the Australian marine fauna. A new species, Periclimenes poriphilus sp. nov., is described and illustrated. It is the first species of its genus to be found actually in a sponge host. Several other Periclimenes species have been reported as associates of sponges. Periclimenaeus arthrodactylus Holthuis, 1952, is reported for the second time only, previously known only from a single specimen collected in the Pulau Sailus Ketjil, Java Sea, Indonesia, in 1899, and new to the Australian fauna. Further specimens of Typton wasini Bruce, 1977 are recorded and Typton nanus Bruce, 1987 is re-assessed as a junior synonym of T. wasini, having been based on a juvenile specimen. An up-dated checklist of the Heron Island pontoniine fauna is also provided.